On the Possibility of Development of the Technology for Managing Seismotectonic Displacements in Fault Zones; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Ruzhich V. V. Valery; Psakhie S. G. Sergey Grigorievich; Shilko E. V. Evgeny Viktorovich; Vakhromeev A. G. Andrey; Levina E. A. Elena (2018, 2018)
Title screen